Analytical and Computational Acoustic Modelling of Side Outlet Muffler and Its Extension in the Modelling of Tapered Side Outlet Muffler - VISHWAKARMA, Sandeep Kumar; PAWAR, Suryappa Jayappa (Archives of Acoustics, 2022)
Mufflers are popular in the suppression of noise levels coming from various machinery. The most common parameters for the evaluation of the performance of mufflers are transmission loss, noise level, and insertion loss. The transmission loss is evaluated for tapered side outlet muffler using finite element analysis without considering the fluid-structure interaction. This study includes analytical modelling and acoustic modelling of the side outlet muffler and transmission loss is in excellent agreement with the reference paper. The feasibility of the acoustic model is also verified with the experimental work on simple expansion chamber muffler. The same finite element analysis is extended for the tapered side outlet muffler. The transmission loss of the tapered side outlet muffler in the given frequency range is found 8.96 dB better than the side outlet muffler. The acoustic pressure level and sound pressure level contours for the tapered side outlet muffler give a clear picture of wave propagation inside the muffler. The effect of the cut-off frequency on the transmission loss of the tapered side outlet muffler can be seen from the contours. This study can be helpful in the determination of the performance of the mufflers in terms of transmission loss, the performance of mufflers above cut-off frequency, and design improvements in the muffler to avoid the higher-order modes of the sound wave.